2002
DOI: 10.1212/wnl.59.6.898
|View full text |Cite
|
Sign up to set email alerts
|

The clock drawing test is a poor screen for very mild dementia

Abstract: Although the clock drawing test can be scored reliably and can differentiate cognitively normal older adults from those with at least mild dementia of the Alzheimer type, it does not appear to be a useful screening instrument for detecting very mild dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
2
14

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 44 publications
(35 reference statements)
7
81
2
14
Order By: Relevance
“…In most of the former studies, the cutoff points of CDTs were provided with the aim of distinguishing a demented state or AD from normal cognition. Recently, Powlishta et al [16], choosing 6 different scoring criteria of the CDT for comparing subjects without altering the cutoff points determined for dementia in each original CDT criterion, have reported that the CDT was a poor screening method for very mild dementia. The sensitivity and specificity for detecting MCI by the CDT obtained in the current study were satisfactory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the former studies, the cutoff points of CDTs were provided with the aim of distinguishing a demented state or AD from normal cognition. Recently, Powlishta et al [16], choosing 6 different scoring criteria of the CDT for comparing subjects without altering the cutoff points determined for dementia in each original CDT criterion, have reported that the CDT was a poor screening method for very mild dementia. The sensitivity and specificity for detecting MCI by the CDT obtained in the current study were satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there has been a dearth of studies examining the utility of the CDT in detecting cognitive deficits in their early stages, in particular MCI. Previous studies yielded conflicting results with limitations in terms of the criteria used for group assignment, the sample size, and the optimal cutoff points for different types of cognitive status [15,16]. Besides, most previous studies emphasized the use of quantitative analyses of the CDT results, leaving detailed qualitative analyses of the results somewhat neglected.…”
Section: Introductionmentioning
confidence: 99%
“…The CDT was used to screen for visuospatial and visuoconstructive disabilities. Two independent scoring systems, the Watson scoring system [39,40] and the AD Cooperative Study scoring system [41], were both adopted to measure the performance of each subject. Given the motor dysfunctions observed in the SCA3 patients, the time taken to complete the drawing task was not included.…”
Section: Methodsmentioning
confidence: 99%
“…Both tests are quick and easy to administer (are paper-andpencil tests) and are recommended by the American Medical Association (AMA) for screening unsafe drivers. However, studies [36,42] have shown the clock drawing test not to be a good screening instrument for detecting the very earliest signs of dementia. One potential draw-back of especially using the trail test for such predictive purposes is that a candidate could get hold of a standard testing sheet and through practice acquaint himself with the spatial configuration of letters and alphabets which would allow him to get a higher but biased score.…”
Section: Discussion On Resultsmentioning
confidence: 99%